The use of designed E-book to improve a concept understanding and practical skill on a mammography machine quality control among radiological technologist students - Moonkum, Nutthapong; Mongkolsuk, Manus; Suwannaporn, Kluaimai; Tochaikul, Gunjanaporn (Research and Practice in Technology Enhanced Learning, 2025)
The fashion in education increasingly integrates technology as learning supporting tool. For undergraduate radiological technologist (RT) students, the concept understanding and practical skills in their professional field have a significant impact on their success. Quality control (QC) of mammography machine is one of the professional responsibilities. A problematic situation in traditional learning process is the lack of devices and the primarily used lecture-style. This makes studying outside classroom and frequent practice more challenging. The purpose of this study was to determine the effectiveness of the developed e-book in RT students about the concept understanding and practical skills of the mammography machine QC, compared with conventional methods. One-hundred and fifteen students were participants, whom were randomized into two groups. The experimental group was able to access the e-book for self-learning, while the control group received only the conventional class on the same topic. The five-scale questionnaires were used to assess student’s satisfaction. A strong increase in the test-scores of the experimental students indicated their in-depth knowledge and better performance in practical and evaluation skills. The experimental group performed better than the control group, with a statistically significant difference at p<0.00001. It also found that the majority of the students agreed that the e-book media was an excellent choice for their self-learning and training. So, it can be concluded that the e-book learning media has a positive influence to students – as a low cost, easily accessible and attractive supporting tool to provide students with the better opportunities for learning and skills-training.